Poly(4-Hydroxybutyrate): Current State and Perspectives - Utsunomia, Camila; Ren, Qun; Zinn, Manfred (Frontiers in Bioengineering and Biotechnology, 2020)
By the end of 1980s, for the first time polyhydroxyalkanoate (PHA) copolymers with incorporated 4-hydroxybutyrate (4HB) units were produced in the bacterium Cupriavidus necator (formally Ralstonia eutropha) from structurally related carbon sources. After that, production of PHA copolymers composed of 3-hydroxybutyrate (3HB) and 4HB [P(3HB-co-4HB)] was demonstrated in diverse wild-type bacteria. The P4HB homopolymer, however, was hardly synthesized because existing bacterial metabolism on 4HB precursors also generate and incorporate 3HB. The resulting material assumes the properties of thermoplastics and elastomers depending on the 4HB fraction in the copolyester. Given the fact that P4HB is biodegradable and yield 4HB, which is a normal compound in the human body and proven to be biocompatible, P4HB has become a prospective material for medical applications, which is the only FDA approved PHA for medical applications since 2007. Different from other materials used in similar applications, high molecular weight P4HB cannot be produced via chemical synthesis. Thus, aiming at the commercial production of this type of PHAs, genetic engineering was extensively applied resulting in various production strains, with the ability to convert unrelated carbon sources (e.g. sugars) to 4HB, and capable of producing homopolymeric P4HB. In 2001, Metabolix Inc. filed a patent concerning genetically modified and stable organisms, e.g., Escherichia coli, producing P4HB and copolymers from inexpensive carbon sources. The patent is currently hold by Tepha Inc., the only worldwide producer of commercial P4HB. To date, numerous patents on various applications of P4HB in the medical field have been filed. This review will comprehensively cover the historical evolution and the most recent publications on P4HB biosynthesis, material properties, and industrial and medical applications. Finally, perspectives for the research and commercialization of P4HB will be presented.